Stumbling on happiness - Gilbert, Daniel Todd. (New York : A.A. Knopf, 2006)
Why are lovers quicker to forgive their partners for infidelity than for leaving dirty dishes in the sink? Why do patients remember long medical procedures as less painful than short ones? Why do home sellers demand prices they wouldn't dream of paying if they were home buyers? Why does the line at the grocery store always slow down when we join it? In this book, Harvard psychologist Gilbert describes the foibles of imagination and illusions of foresight that cause each of us to misconceive our tomorrows and misestimate our satisfactions. Using the latest research in psychology, cognitive neuroscience, philosophy, and behavioral economics, Gilbert reveals what we have discovered about the uniquely human ability to imagine the future, our capacity to predict how much we will like it when we get there, and why we seem to know so little about the hearts and minds of the people we are about to become.--From publisher description.
Acknowledgments -- Foreword -- pt. 1. Prospection -- 1. Journey to Elsewhen -- pt. 2. Subjectivity -- 2. The view from in here -- 3. Outside looking in -- pt. 3. Realism -- 4. In the blind spot of the mind's eye -- 5. The hound of silence -- pt. 4. Presentism -- 6. The future is now -- 7. Time bombs -- pt. 5. Rationalization -- 8. Paradise glossed -- 9. Immune to reality -- pt. 6. Corrigibility -- 10. Once bitten -- 11. Reporting live from tomorrow -- Afterword -- Notes -- Index.
Includes bibliographical references and index.
1 2
Keywords: Happiness